2004
DOI: 10.1158/0008-5472.can-03-2194
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Carcinoma Expresses the NKG2D Ligand Letal and Promotes the Survival and Expansion of CD28− Antitumor T Cells

Abstract: The role of the NKG2D immunoreceptor and its ligands in antitumor immune response is incompletely understood. Here, we report that effector immune cells infiltrating ovarian carcinoma are mostly CD8؉ lymphocytes lacking CD28 but expressing the NKG2D costimulatory receptor. Human ovarian carcinoma expresses the novel NKG2D ligand lymphocyte effector cell toxicity-activating ligand (Letal). Letal was found to be an independent prognosticator of improved survival in advanced ovarian cancer. Higher levels of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 31 publications
(49 reference statements)
0
58
2
2
Order By: Relevance
“…As expected, sorted tumor ECs and HUVECs also formed functional capillaries in Matrigel (HUVECs formed large plugs and were CFSE dim , indicating proliferation), whereas CD45 ϩ VE-cadherin Ϫ cells and did not partake in the formation of blood vessels (Figure 2A and Supplementary Figure 1). Control plugs injected with activated CD8 ϩ T cells 14 were reabsorbed after 2 weeks, consistent with the absence of vessel formation. Finally, select tumors exhibited capillary structures harboring CD45 ϩ cells that coexpressed VE-cadherin ( Figure 2C).…”
Section: Resultsmentioning
confidence: 52%
“…As expected, sorted tumor ECs and HUVECs also formed functional capillaries in Matrigel (HUVECs formed large plugs and were CFSE dim , indicating proliferation), whereas CD45 ϩ VE-cadherin Ϫ cells and did not partake in the formation of blood vessels (Figure 2A and Supplementary Figure 1). Control plugs injected with activated CD8 ϩ T cells 14 were reabsorbed after 2 weeks, consistent with the absence of vessel formation. Finally, select tumors exhibited capillary structures harboring CD45 ϩ cells that coexpressed VE-cadherin ( Figure 2C).…”
Section: Resultsmentioning
confidence: 52%
“…T cells are the only component in the ovarian carcinoma microenvironment capable of exerting spontaneous immune pressure against tumor progression (12,14,15). Thus, we next determined whether protective antitumor T cell responses are elicited in response to treatment with siRNA-PEI nanocomplexes.…”
Section: Figurementioning
confidence: 99%
“…Correspondingly, we recently demonstrated that the elimination of such tumor-associated DCs delays ovarian cancer progression by boosting antitumor immunity (13). Thus, it is likely that the release of this crucial immunosuppressive brake enables the awakening of tumor-infiltrating effector lymphocytes, the only known element of the ovarian carcinoma microenvironment capable of exerting spontaneous immune pressure against tumor progression (12,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…We sought to extend these observations by examining requirements for NKG2D signaling in killing of autologous tumor by CD8 ϩ T cells activated and expanded from human patients undergoing cancer therapy. A novel NKG2D ligand, termed Letal, has recently been found to be expressed by ovarian carcinoma patients (41). Patients with ovarian cancer undergoing surgical resection of their tumor were selected as sources of tumor targets for in vitro cytolysis studies.…”
Section: Nkg2d Is Required For Cytolysis Of Autologous Tumor By Activmentioning
confidence: 99%